135k views
5 votes
6y + 9 = 45 asap answer

User Sbegaudeau
by
4.7k points

2 Answers

3 votes

Answer:

y=6

Explanation:

6y+9=45

-9 -9

6y=36

y=6

User OrangeDog
by
4.4k points
4 votes

Answer:

y = 7

Explanation:

Simplifying

6y + 3 = 45

Reorder the terms:

3 + 6y = 45

Solving

3 + 6y = 45

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.

3 + -3 + 6y = 45 + -3

Combine like terms: 3 + -3 = 0

0 + 6y = 45 + -3

6y = 45 + -3

Combine like terms: 45 + -3 = 42

6y = 42

Divide each side by '6'.

y = 7

Simplifying

y = 7

User Petr Lazarev
by
4.7k points